2017
DOI: 10.3892/mmr.2017.7364
|View full text |Cite
|
Sign up to set email alerts
|

Stable silencing of TIPE2 reduced the Poly I:C-induced apoptosis in THP-1 cells

Abstract: The present study aimed to determine the underlying mechanism of toll‑like receptor (TLR) agonist polyinosinic:polycytidylic acid (Poly I:C)‑induced apoptosis in THP‑1 cells following silencing the expression of tumor necrosis factor α‑induced protein 8‑like 2 (TIPE2). THP‑1 cells were incubated with different concentrations of the TLR agonist. Following incubation, reverse transcription‑quantitative polymerase chain reaction was performed to quantify the mRNA expression of TIPE2. Lentiviral technology was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The result was consistent with down-regulated expression of TIPE2 in M1 macrophages that can release neutrophilic inflammation factors and aggravate neutrophilic inflammation in asthma ( 3 ). TIPE2 was shown to inhibit macrophage apoptosis and M1 phenotype polarization in vitro by decreasing the levels of monocyte chemoattractant protein (MCP)-1, TNF-α, IL-6, IL-1β, and IL-12 ( 19 , 37 , 38 ). TIPE2 may inhibit neutrophilic inflammation in asthma.…”
Section: Discussionmentioning
confidence: 99%
“…The result was consistent with down-regulated expression of TIPE2 in M1 macrophages that can release neutrophilic inflammation factors and aggravate neutrophilic inflammation in asthma ( 3 ). TIPE2 was shown to inhibit macrophage apoptosis and M1 phenotype polarization in vitro by decreasing the levels of monocyte chemoattractant protein (MCP)-1, TNF-α, IL-6, IL-1β, and IL-12 ( 19 , 37 , 38 ). TIPE2 may inhibit neutrophilic inflammation in asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Certain clinical studies have observed that, during the development of GC, the expression profiles of specific biomolecules change. Such changes in expression may serve a key role in tumor progression, including the processes of cell proliferation (٦,١٠,١٨,٢٢,23), motility ( 24 ), adhesion ( 25 ), apoptosis and tissue inflammation. As an inflammatory inhibitor, TIPE2 not only induces cell death, but also inhibits Ras-induced tumor formation, providing a molecular bridge from inflammation to cancer.…”
Section: Discussionmentioning
confidence: 99%
“…45,46 In TIPE2-deficient myeloid cells, polyinosinic-polycytidylic acid (Poly(I:C))mediated dsRNA signaling pathway was overactive, while Poly(I:C) was capable of downregulating TIPE2 expression mediated by downstream cytokines. 47 Furthermore, TIPE2 was found to regulate Rac1-signal transducer and activator of transcription 3 (STAT3) and ERK1/2 signaling pathways and downregulate the expression levels of cyclin D1 and cyclin D3 in mice model of injury-induced restenosis disease 48 (Figure 2).…”
Section: Downstream Effect Factors Of Tipe2mentioning
confidence: 99%